KOMUNIKASI INOVASI JAKARTA EVOLUTION (JAKEVO) DAN KINERJA PEGAWAI PELAYANAN TERPADU SATU PINTU (PTSP) WILAYAH JAKARTA BARAT - Zirli Nur Shafa Widad (2021)
One of the challenges of organizational communication is environmental changes caused by various things. The current Covid 19 pandemic has a significant impact on all aspects of life, including health, economics, and social life, as well as the DKI Jakarta PTSP Service which has made changes through the JakEVO service innovation where employees can provide services during working hours to reduce the spread of the Covid 19 virus. This research's purpose is to prove the effect of JakEVO innovation communication on the performance of PTSP employees in the West Jakarta area by testing the theory of Everett Rogers's organizational innovation stages. This research use survey as a method by distributing questionnaires to all PTSP employees in Kebon Jeruk District and Grogol Petamburan District. The results showed that there was a significant effect between the JakEVO innovation communication on the performance of PTSP employees in the West Jakarta area. These results are based on the calculation of the regression test results obtained the influence of the JakEVO innovation communication on the performance of PTSP employees in the West Jakarta area in the amount of 0.520. These results are supported by the hypothesis testing, Ho is rejected and Ha is accepted, which means that JakEVO Innovation Communication has an effect on Employee Performance.